Colonial drivers and cultural protectors of brain health among Indigenous peoples internationally - Henderson, Rita; Furlano, Joyla A.; Claringbold, Shayla Scott; Cornect-Benoit, Ashley; Ly, Anh; Walker, Jennifer; Zaretsky, Lisa; Roach, Pamela (Frontiers in Public Health, 2024)
Despite relatively higher rates of dementia among Indigenous populations internationally, research into drivers of disparities in brain health and cognitive function has tended to focus on modifiable risk factors over cultural understandings and contextual determinants. By seeking to characterize social and cultural factors that shape brain health and cognition in Indigenous populations, this mini scoping review expands prevailing schools of thought to include Indigenous knowledge systems. This reveals important gaps in culturally aligned care. It also reclaims horizons for research important to Indigenous Peoples that have garnered diminished attention in biomedical approaches. Twenty-three sources were included for data extraction. This synthesis of 23 sources includes health communication about dementia, health provider knowledge about Indigenous health, culturally relevant screening and assessment tools, and culturally grounded care models. Much of the focus is currently still on modifiable risk factors that reside at individual factors, whereas attention to wider social factors that impact populations is needed, as stressors through isolation, discrimination, and unequal care are widely reported. Going forward, identifying structural barriers to living well and recognizing the importance of connection to culture will benefit both Indigenous and non-Indigenous understandings of brain health.